2018
DOI: 10.1177/0972150918791378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subliminal Advertising on Consumer Buying Behaviour: An Empirical Study on Young Indian Consumers

Abstract: The main aim of this study is to examine the impact of subliminal messages in TV advertisements on consumer behaviour. Though there are number of ways through which impact of subliminal advertisements can be unearthed, in the current study, behavioural approach was adopted, which included discussion on case study (group discussion on subliminal ads) followed by response on a questionnaire. A sample of 390 respondents was chosen from Kashmir division through multi-stage random sampling framework, which, by and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…From this perspective, this study has concluded that brand awareness created by advertisements influences the buying behavior of cosmetics consumers. Sofi et al (2018) stated that advertisement substantially predicts consumer buying behavior, while such an association becomes stronger when advertisement actively produced positive outcomes. In the same sense, this study has proved the mediation effect of brand awareness between advertisement and consumer buying behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, this study has concluded that brand awareness created by advertisements influences the buying behavior of cosmetics consumers. Sofi et al (2018) stated that advertisement substantially predicts consumer buying behavior, while such an association becomes stronger when advertisement actively produced positive outcomes. In the same sense, this study has proved the mediation effect of brand awareness between advertisement and consumer buying behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Advertisement is a mode of communication marketing through electronic or print media that persuade the customer to continue or adopt some action by paid content (Cheah et al, 2019). According to Sofi et al (2018), it is a non-personal way of sharing information related to a product produced by a sponsor with the help of media. Similarly, Ayanwale et al (2005) proposed that advertising is a paid, nonpersonal way in which concepts, products or services, ideas, and information are publicized through media (verbal, visual, and te't) and identified promoter influence behavior.…”
Section: Advertisementmentioning
confidence: 99%
“…Another relevant context to discuss this principle is social media through which marketing has become an effective way of influencing people [ 123 ]. Students would perhaps benefit from knowing that the effect of unconsciously perceived sensory stimuli (subliminal priming) on human behavior is increasingly being used in political campaigns, product promotion and marketing across many areas of public interest to influence voters and consumers [ 124 ] beyond their awareness, and young people are particularly susceptible [ 125 ]. Consequently, introducing this principle in compulsory education is becoming more important since current technology is increasingly designed to impose consumer addiction by targeting the brain’s emotional and reward systems [ 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a meta-analysis carried out in the 1990s (Trappey, 1996) found that the effectiveness of subliminal advertising is very low since each individual has different perceptions, the study by Hsu & Chen (2020) found this effect quite significant, using neuromarketing techniques. Furthermore, recent studies have found the influence of subliminal messages on the purchasing behavior of consumers, making them make purchases after being exposed to these messages in advertisements (Sofi et al, 2018), as well as indicating that the field of subliminal stimuli needs continuous research to really get a deeper understanding of how reliable this methodology can be (Madan et al, 2021). Thus, it can be understood that not only video can influence consumer behavior, but also the subliminal messages that are linked to it.…”
Section: Filmmakingmentioning
confidence: 99%